Critical loads of nitrogen deposition and critical levels of atmospheric ammonia for semi-natural Mediterranean evergreen woodlands - Pinho, P; Theobald, M R; Dias, T; Tang, Y S; Cruz, C; Martins-Loução, M a.; Máguas, C; Sutton, M; Branquinho, C (Biogeosciences, 2012)
Nitrogen (N) has emerged in recent years as a key factor associated with global changes, with impacts on biodiversity, ecosystems functioning and human health. In order to ameliorate the effects of excessive N, safety thresholds such as critical loads (deposition ﬂuxes) and levels (concentrations) can be established. Few studies have assessed these thresholds for semi-natural Mediterranean ecosystems. Our objective was therefore to determine the critical loads of N deposition and long-term critical levels of atmospheric ammonia for semi-natural Mediterranean evergreen woodlands. We have considered changes in epiphytic lichen communities, one of the most sensitive comunity indicators of excessive N in the atmosphere. Based on a classiﬁcation of lichen species according to their tolerance to N we grouped species into response functional groups, which we used as a tool to determine the critical loads and levels. This was done for a Mediterranean climate in evergreen cork-oak woodlands, based on the relation between lichen functional diversity and modelled N deposition for critical loads and measured annual atmospheric ammonia concentrations for critical levels, evaluated downwind from a reduced N source (a cattle barn). Modelling the highly signiﬁcant relationship between lichen functional groups and annual atmospheric ammonia concentration showed the critical level to be below 1.9 µg m−3 , in agreement with recent studies for other ecosystems. Modelling the highly signiﬁcant relationship between lichen functional groups and N deposition showed that the critical load was lower than 26 kg (N) ha−1 yr−1 , which is within the upper range established for other semi-natural ecosystems. Taking into account the high sensitivity of lichen communities to excessive N, these values should aid development of policies to protect Mediterranean woodlands from the initial effects of excessive N.
Keywords: atmospheric ammonia; Critical levels; Critical loads; lichen functional-groups; Mediterranean evergreen woodlands (voyant); n deposition